PENGARUH PENGGUNAAN MEDIA VIDEO INTERAKTIF TERHADAP HASIL BELAJAR SISWA KELAS XI DI SMAN 1 PAINAN - Hafizah Sukmawati; Afdhal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims (1) to determine the learning outcomes of students in the control class using printed books on population dynamics material at SMAN 1 Painan (2) to determine the learning outcomes of students in the experimental class using interactive video media on population dynamics material (3) to determine the effect of using interactive video media on student learning outcomes on population dynamics material at SMAN 1 Painan. The research method used in this study is the Quasi Experimental Research method (quasi-experimental research) with a Nonequivalent Control Group Design research design with a control group and an experimental group. The population in this study was all grade XI at SMAN 1 Painan. Sampling was carried out using a purposive sampling technique. The sample used in this study were students of XI F1 as the control class and students of XI F2 as the experimental class using interactive video media. Data collection used pretest and posttest instruments in the form of multiple choices that had gone through validity tests, difficulty tests and discriminatory power tests. Data analysis techniques used were validity tests, difficulty tests, discriminatory power tests, normality tests, homogeneity tests, and hypothesis tests. The results of this study indicate that: (1) The use of interactive video media in the geography learning process on population dynamics material has a positive influence on student learning outcomes (2) This is proven by the average posttest value in the experimental class of 85 and the average value in the control class of 65. From the hypothesis test (T test) shows a sig value of 0.000 < 0.05, and it can be concluded that there is a significant difference in student learning outcomes between the control class and the experimental class. Thus, it can be concluded that the independent variable (X), namely the use of interactive video media on population dynamics material, has an influence on the dependent variable (Y), namely the learning outcomes of class XI students at SMAN 1 Painan.